Quantitative intramuscular myoelectric activity of lumbar portions of psoas and the abdominal wall during cycling - Juker, D.; McGill, S.; Kropf, P. (Journal of Applied Biomechanics, 1998)
The purpose of this study was to quantify activation using intramuscular EMG from lumbar psoas and the three layers of the abdominal wall during several styles of cycling: normal posture (slightly flexed), upright posture, racing in flexed posture, standing up from the saddle, and standing during maximal sprint effort. Lumbar erector spinae and rectus femoris were also monitored with surface electrodes. Results demonstrated that the activity patterns were influenced by the style of cycling. Furthermore, psoas activity peaked at 14% of MVC (or less) during the upstroke phase of normal cycling but became much more active at TDC during flexed cycling (approximately 30% MVC) and approached 60% of MVC during sprinting. Generally, the abdominal wall was activated to relatively low but continual levels except during standing and sprinting. Erector spinae activity was very low at less than 5% MVC throughout the cycle until standing or sprinting styles were adopted. These normalized and scaled data on deep muscle activity during ergometer cycling provide insight into the functioning of these muscles; this information can be used to prescribe rehabilitation and training programs and can help biomechanists understand muscle activity associated with cycling.